Output regulation for stochastic delay systems under asynchronous switching with dissipativity. Issue 2 (1st February 2021) - Jin, Cui-Li; Li, Li-Li; Wang, Rui; Wang, Qing-Guo
Abstract : This paper is concerned with output regulation for a class of switched stochastic delay systems based on the dissipativity property. We address one important practical issue: switching between the regulators is not synchronous with but delayed from switching between the systems due to the limited speed of information transmission and control action. The average dwell time (ADT) method is used to design switching signals and asynchronous regulators. The error-dependent integral term is added to the Lyapunov–Krasovskii (L–K) functional to make better use of the delay information. An auxiliary matrix is introduced to gain higher degree of freedom to achieve both the ADT condition and the dissipativity condition. The solvability conditions are derived using linearisation techniques, and they also give the relations between ADT and upper bound of delays. Simulation examples are provided to testify the feasibility and validity of the proposed approach.